La banca colombiana frente al pilar I del acuerdo de Basilea II (2006)
The importance of Colombian financial system for the economy of the country requires of a effective supervision that it demands to the financial organizations to maintain levels of capital sufficient todiminish the losses generated by breaches of counterpart. The principles established by the Committee of Basel II (main forum of international cooperation in the matter of banking regulation) serves as reference for the superintendents and others public authorities within the countries and internationally, helping to establish solid financial systems able to absorb the situations of crisis and to serve as shock absorbers of the depressive effects on the economies and the markets. In Colombia at December 2004 the banking establishments are fulfilling the level of solution demanded by the Financial Supervision, because the calculation model does not include the operative risk that it demands Basel II, if it is applied, it is observed that more of 50% of the this banking organizations would not fulfill the requirement of minimum level of capital. To improve this situations it would be required a capital over those of 433 billion of Colombian pesos, in addition to the implementation of a strategies for its fortification. This has caused and adjustmentof the Colombian financial sector in the 2005-2006, through fusions and acquisitions.